The role and use of management accouting systems (MAS) in family firms: a case study - Bracci, Enrico; Maran, Laura (Piccola Impresa / Small Business, 2012)
Medium and small family firms are a fundamental element for the Italian economic development and wealth. One of the main reasons of failure of this type of firm is the business succession, within the family members. The literature considers the business succession as a natural and progressive phenomenon that is linked to both the long-term survival of the firm and/or an increasing efficiency. Despite the vast literature on the topic, a few studies try to focus further dimensions of the business succession as the role of management accounting systems (MASs) in connection with trust and organizational routines. The aim of the present research is to deepen a process of business succession, with a specific focus on both the inter-generational relationships and their influence on the role played by MASs. A qualitative methodology will be used to conduct a longitudinal case-study, using a deductive-inductive-deductive approach, that is typical of the business administration studies. The expected results of the research concern the identification and definition of the “rational” (tied to the firm “efficiency”) and “familiar” (tied to the trust among family members) discourses and the way in which the MASs are involved in this process. The present study will point out how the inter-generational succession is influenced by both a rational/ deterministic planning and a set of family relationships. Only the whole consideration of those factors would shed light on the functioning of the inter-generational succession and predict its effectiveness